Factors Affecting the Banking Habit of Urban People - Gautam, Madhusudan (Management Dynamics, 2022)
Good banking habits are crucial for managing household finances and achieving financial stability. This study aims to examine the major factors that affect the banking habit of urban people. The survey was carried out by distributing structured questionnaires to people of various ages, genders, occupations, and qualifications in Ghorahi Municipality, Dang District- a mid-western part of Nepal. The study followed the descriptive cum casual research design and concluded that convenience, availability, and security have positive effects on banking habits. But awareness level and motivation factors do not have any linkage with the banking habit of urban people. It may be the reason for the similar nature of products and services offered by banks, the increased financial literacy rate, and the financial knowledge of urban people. Thus, the results of this study are helpful for banks to formulate and adopt relevant strategies to increase banking habits.